Pengaruh Profitabilitas dan Leverage dengan Reaksi Pasar Terhadap Kinerja Saham Sebagai Variabel Moderator - Andi Nurhaeda; Fanesa Isalia Minanda Syaifuddin (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
The capital market plays a strategic role in the economy as a means for companies to obtain long-term funding. Profitability, leverage, and firm size are fundamental factors that can influence market reaction. This study aims to analyze the effect of profitability and leverage on market reaction and examine the moderating role of stock performance. The data used is secondary data obtained from the annual financial reports of companies listed on the Indonesia Stock Exchange (IDX) for the period of 2022 to 2024. The results show that profitability have a positive and significant effect on market reaction, while leverage has a negative and significant effect on market reaction. However, stock performance failed to moderate the effect of profitability and leverage on market reaction. These findings support the Signaling Theory and Trade-Off Theory in the context of the Indonesian capital market. The implication of this research is that companies need to improve profitability and strengthen their financial structure to enhance investor confidence and improve market positioning.